Impressive response to nivolumab of non‐small‐cell lung cancer containing sarcomatoid components. Issue 8 (20th August 2019) - Ota, Takahiro; Niho, Seiji; Kirita, Keisuke; Ishii, Genichiro; Tsuboi, Masahiro; Goto, Koichi
Abstract : We present two cases of pulmonary pleomorphic carcinoma (PPC) treated with Nivolumab. A 57‐year‐old man presented with a 3.5‐cm mass in the left lower lobe. Left lower lobectomy and lymph node dissection were performed. Histological diagnosis was stage IIIA (pT2bN2M0) PPC. The tumour relapsed two months later and he was treated with carboplatin and paclitaxel, but his condition became progressive and nonresponsive after one cycle. We used nivolumab as second line. Repeat chest X‐ray showed impressive reduction of relapse lesions seven days after the start of nivolumab therapy. Our second case is a 50‐year‐old man who presented with a 3.7‐cm mass in the right lower lobe and submucosal tumour in the colon. Endobronchial ultrasound‐guided transbronchial needle aspiration biopsy (EBUS‐TBNA) and colon biopsy yield the diagnosis of PPC and metastatic colon cancer. He was treated with cisplatin plus pemetrexed. His disease proved resistant and we used nivolumab as second line. He showed partial response following four cycles. Abstract : We describe two patients with advanced non‐small‐cell lung cancer (NSCLC), including one in whom the definitive diagnosis of pulmonary pleomorphic carcinoma (PPC) was made by histopathology of the resected tumour and another in whom the diagnosis of "favor adenocarcinoma containing sarcomatoid components" was made by tissue biopsy. Both were resistant to first line platinum‐based chemotherapy, but responded dramatically to second line nivolumab therapy.